Video Poems and the Discourse of the Image – Towards New Literary and Digital Genres - arioua, Souad; ben hmimd, Manel (El Omda in Linguistics and Discourse Analysis, 2022)
This article aims to examine the positioning of literary genres within the context of globalization and digitalization. As technology has come to dominate all aspects of life, it has profoundly affected literature, which has shifted from print-based forms to virtual environments, thereby transforming its medium of transmission. Digital literature thus represents the latest stage in the evolution of literary production, benefiting from the possibilities offered by technological and virtual environments to enhance its aesthetic and structural components. This research paper seeks to uncover the characteristics of digital texts through the analysis of video poems, particularly those of Dr. Labiba Khammar, such as Bishara, A Message of Mourning, The Mood of Your Lilac Night, The Garden of Words, The Tree of Estrangement, and The Dance of Letters, among others. These works are considered an emerging digital literary genre in which the written word is reinforced by image, sound, music, movement, and various technological media.